2017
DOI: 10.1177/1010428317691000
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of junctional adhesion molecule-A and EphB2 predicts poor survival in lung adenocarcinoma patients

Abstract: Junctional adhesion molecules are important components of tight junctions, and Eph/ephrin proteins constitute the largest family of receptor tyrosine kinases. Both junctional adhesion molecules and Eph/ephrin are involved in normal tissue development and cancer progression. However, the expression levels and clinical significances of junctional adhesion molecule-A, a member of junctional adhesion molecules, and EphB2, a member of Eph/ephrin family, in lung adenocarcinoma patients are unclear. Therefore, in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
6
18
0
Order By: Relevance
“…Furthermore, EFNA3, EFNB1, EFNB2, and EPHB2 showed a signi cant correlation with OS and PFS in LUAD patients. Previous studies con rmed that EPHB2 was overexpressed in LUAD tissue, and is an independent prognostic biomarker [20]. This is consistent with the results presented here.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, EFNA3, EFNB1, EFNB2, and EPHB2 showed a signi cant correlation with OS and PFS in LUAD patients. Previous studies con rmed that EPHB2 was overexpressed in LUAD tissue, and is an independent prognostic biomarker [20]. This is consistent with the results presented here.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our TCGA analysis (Figure 2A), EPHB2 overexpression in several other cancer types has been reported to correlate with decreased patient survival (90,91). We further found that the correlation of EPHB2 overexpression in HNSCC tumors with poor prognosis was even higher if the exosome secretion regulator cortactin (31) was also overexpressed, suggesting that exosomal EPHB2 may drive tumor aggressiveness.…”
Section: Discussionsupporting
confidence: 90%
“…IS was graded as 0 (negative), 1 (weak), 2 (moderate) and 3 (strong). PKM2 expression was calculated based on the equation: Intensity distribution (ID) = AP × IS [32].…”
Section: Evaluating Results Of Pkm2 Expressionmentioning
confidence: 99%